India - Ludhiana - Punjab - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
At the Punjab Agricultural University., India. CCAFS is performing research in several parts of South Asia. The pictures in this set were taken in relation to the making of the farmer testimonial videos, on farmer adaptation and mitigation to climate change.